Konsep Serta Desain Strategi, Metode dan Rancangan Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Teori Belajar - Junia Fitri; Maulana M; Nur Annisa; Yenni Aprianti (Malewa: Journal of Multidisciplinary Educational Research, 2026)
Islamic Religious Education (PAI) learning requires appropriate strategies and methods so that educational objectives can be achieved effectively in the cognitive, affective, and psychomotor domains. This article aims to identify various types of learning strategies and methods, design learning based on learning theories, and develop instructional strategies for PAI. This study employs a qualitative descriptive approach through the analysis of behavioristic, cognitive, and humanistic learning theories. The findings indicate that expository, inquiry, cooperative learning, Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Contextual Teaching and Learning (CTL) strategies can be implemented according to instructional needs. Behavioristic theory is effective in shaping worship habits, cognitive theory supports the understanding of religious concepts, while humanistic theory plays a role in developing religious character. The combination of these three theories results in PAI learning that is active, creative, enjoyable, and meaningful.